Incomplete penetrance of GLMN gene c.395–1G>C mutation in a family with glomuvenous malformations. (25th June 2014) - Borroni, Riccardo G.; Grassi, Sara; Diegoli, Marta; Grasso, Maurizia; Arbustini, Eloisa
Abstract Glomuvenous malformations (GVMs, OMIM 138000) are hamartomas presenting in childhood as multiple, bluish, soft papules and nodules that tend to grow slowly in size and number with age. They are caused by autosomal dominant mutations in glomulin (GLMN) gene; penetrance varies from 80% at 20 to about 100% at age 30 years. We report on the c.395–1G>C mutation of GLMN gene in two siblings showing variable penetrance.